Automobilske gume i njihovo održavanje - Štrumberger, Nada; Džanić, Husein (Promet - Traffic&Transportation, 2012)
The development of the automobile industry has invigorated the development and advancement of the tire manufacturers. Considering the fact that the tire is a major factor of traffic safety it should be secured proper maintenance and inspection.